2022
DOI: 10.1007/s12517-022-10072-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and equilibrium studies on the zinc adsorption–desorption characteristics of some promising biochars in aqueous solutions

Abstract: The present research aimed at investigating zinc (Zn) sorption capacity of the biochars derived from apple wood (WB) and rice straw (RB) feedstocks at two 300 and 600 °C pyrolysis temperatures (WB300, WB600, RB300 and RB600, respectively) in aqueous solutions. Kinetic and equilibrium sorption experiments were conducted via batch technique. In equilibrium adsorption experiments, the study used the concentration range of 5-200 mg Zn L -1 and focused on the solution pH effect on Zn adsorption in biochars under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Each heavy metal ion has a limiting pH, and when the solution pH exceeds its limiting pH, the metal ion will exist in other forms and produce precipitation. Masoumeh et al studied biochars from apple wood (WB) and rice straw (RB) and found that Zn adsorption increasing the initial pH of solutions from 4 to 6 increased the Zn adsorption in RB600, RB300, and WB600 [41]. These results indicate the high efficiency of FS500 in treating Zn-contaminated liquids when the pH is higher than 3 and the potential application of FS500 in PRB systems.…”
Section: Influence Of Initial Solution Ph On Zn Adsorptionmentioning
confidence: 99%
“…Each heavy metal ion has a limiting pH, and when the solution pH exceeds its limiting pH, the metal ion will exist in other forms and produce precipitation. Masoumeh et al studied biochars from apple wood (WB) and rice straw (RB) and found that Zn adsorption increasing the initial pH of solutions from 4 to 6 increased the Zn adsorption in RB600, RB300, and WB600 [41]. These results indicate the high efficiency of FS500 in treating Zn-contaminated liquids when the pH is higher than 3 and the potential application of FS500 in PRB systems.…”
Section: Influence Of Initial Solution Ph On Zn Adsorptionmentioning
confidence: 99%